MULTILOCUS SEQUENCE TYPING OF CARBAPENEM RESISTANT PSEUDOMONAS AERUGINOSA ISOLATES FROM PATIENTS PRESENTING AT PORT ELIZABETH HOSPITALS, SOUTH AFRICA - Annear, D.; Black, J.; Govender, S. (African Journal of Infectious Diseases (AJID), 2017)
Background: Pseudomonas aeruginosa is an important nosocomial pathogen that exhibits multiple drug resistance with increasing frequency, especially to carbapenems making patient treatment difficult. Carbapenem-resistance may be caused by porin gene mutations, active drug efflux, and carbapenemase production. This study evaluated the incidence of genes responsible for carbapenemase production in carbapenem-resistant Pseudomonas aeruginosa and assessed the genetic relatedness of the isolates by multi locus sequence typing (MLST). Materials and Methods: Identification and antimicrobial susceptibility testing of P. aeruginosa isolates (n=234) by the VITEK 2 system detected 81 carbapenem resistant P. aeruginosa isolates. PCR and DNA sequencing were used to screen isolates for three metallo-β-lactamase encoding genes. MLST included amplification of seven housekeeping genes and sequence type alignment using the online P. aeruginosa MLST database. Results: Only the blaVIM-2 gene was detected in 15 of the 81 carbapenem resistant isolates. MLST indicated six different novel sequence types among the blaVIM-2 positive P. aeruginosa isolates with the majority of the isolates (9/15) containing identical allelic profiles of the sequence type allocated ST1 (provisionally assigned sequence type, awaiting addition of new sequence types to PubMLST database). Five of these ST1 isolates were from patients and an environmental sample in the same hospital ward suggesting an environmental reservoir. Carbapenem resistance in the blaVIM-2 negative isolates may be due to other mechanisms. Conclusion: The incidence of genes responsible for carbapenemase production in carbapenem-resistant Pseudomonas aeruginosa and genetic relatedness of these isolates in public healthcare facilities within the Port Elizabeth area is of concern and requires further investigation.